Measuring women's experiences of maternity care: A systematic review of self-report survey instruments. Issue 3 (May 2021) - Beecher, Claire; Greene, Richard; O'Dwyer, Laura; Ryan, Ethel; White, Mark; Beattie, Michelle; Devane, Declan
Abstract: Background: Recognition of the measurement of women's experiences of their maternity care as a critical component of care quality evaluation has led to a proliferation of instruments to measure this concept. However, the suboptimal methodological and psychometric quality of these instruments, or the lack of reporting of same, hinders the credibility and efficient use of the arising results, which often serve as an indicator for the direction of limited resources within maternity services. Aim: To review systematically and critically appraise self-report survey instruments measuring women's experiences of their maternity care. Methods: A systematic review was conducted using comprehensive searches of the CINAHL, OVID MEDLINE and EMBASE citation databases. Inclusion and exclusion criteria were applied, and a stepped approach employed to facilitate evaluation of the methodological and psychometric quality of included instruments. Findings: 4905 records were obtained from database searches. Additional records were obtained via reference checking and by expert suggestion. Following stepped screening, 40 papers related to 20 instruments are included in this review. Findings indicate that evidence of the methodological and psychometric quality have not been reported for many included instruments. Conclusions: Published evidence of the methodological and psychometric quality of self-report survey instruments to evaluate women's experiences of their maternity care is lacking. The conduct and reporting of future development processes of such instruments can be improved. Systematic review PROSPERO registration : CRD42018105325.